VET research and international cooperation : unlocking the potential of VET research and cross-national partnerships for the development of VET systems - Huebler, Friedrich [Verfasser]; Schröder, Thomas [Verfasser]; Thomann, Birgit [Verfasser] (My University, 2025)
„The pivotal role of vocational education and training (VET) research for the design of VET policies and the development of VET systems is generally undisputed. Despite this, the establishment of efficient research capacities and the implementation of Vocational Education as an autonomous academic discipline along with adequate capacity building of researchers and research institutions mostly remain under-appreciated. Institutionalised VET research at universities or research institutes and being an indispensable basis for adapting VET to technical and socio-economic developments […] is rarely perceived as an integral part of international VET cooperation. This is a problem because it means that not only are data and research findings missing in countries but also the scientists and scholars who can exchange knowledge with the international community and support the transfer into VET practice and the development of VET systems in their national context and culture. As part of their mandates, the UNESCO-UNEVOC International Centre for Technical and Vocational Education and Training (TVET), the Federal Institute for Vocational Education and Training (BIBB) as a centre of competence for VET in Germany and an active UNEVOC Network member, and the UNESCO Chair on TVET and Competence Development for the Future of Work at TU Dortmund University in Germany are involved on an international level in the development of VET systems and VET research. Drawing on this experience, the article will underline the relevance of VET research in reforming VET systems and highlight two flagship initiatives geared towards strengthening the interaction between VET research, VET policy, and transfer into VET practice through policy dialogue and peer learning at both the regional and global level.“ (authors‘ abstract; BIBB-Doku)

Die AutorInnen schildern in ihrem Beitrag das Potenzial von internationaler Kooperation für die Berufsbildungsforschung und für die Entwicklung des Berufsbildungssystems. (Hrsg.; BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; S 3.5 Institutionen der Berufsbildungsforschung & -politik; 370; Berufsbildung; Berufsbildungsforschung; Internationale Zusammenarbeit; UNESCO; UNEVOC; Bundesinstitut für Berufsbildung; Südostasien